Factors Associated with High Prevalence of Intestinal Protozoan Infections among Patients in Sana'a City, Yemen - Alyousefi, Naelah A. (Public Library of Science, 2011)
BACKGROUND: Intestinal protozoan diseases in Yemen are a significant health problem with prevalence ranging from 18% to 27%. The present study is a cross-sectional study aimed at determining the factors associated with the high prevalence of intestinal protozoan infections among patients seeking health care in Sana'a City, the capital of Yemen. METHODOLOGY/PRINCIPAL FINDINGS: Stool samples were collected from 503 patients aged between 1 and 80 years old; 219 were males and 284 females. Biodata were collected via pretested standard questionnaire. Faecal samples were processed and examined for (oo)cysts or ova using a wet mount preparation after formal-ether concentration technique. Cryptosporidium oocysts were detected using the Ziehl-Neelsen staining technique. The overall prevalence of intestinal protozoan infections was 30.9%. Infection rates of Giardia duodenalis, Entamoeba histolytica/dispar and Cryptosporidium were 17.7%, 17.1% and 1%, respectively. Other parasites detected included Ascaris lumbricoides (2.4%), Schistosoma mansoni (0.3%), Hymenolepis nana (1.4%) and Enterobius vermicularis (0.4%). Multivariate analysis using forward stepwise logistic regression based on intestinal protozoan infections showed that contact with animals (OR = 1.748, 95% CI = 1.168–2.617) and taking bath less than twice a week (OR = 1.820, 95% CI = 1.192–2.779) were significant risk factors of protozoan infections. CONCLUSIONS/SIGNIFICANCE: This present study indicated that intestinal protozoan infections are still a public health problem in Yemen, with Giardia and Entamoeba infections being most common. Statistical analysis indicated that low personal hygiene and contact with animals were important predictors for intestinal protozoan infections. As highlighted in this study, in order to effectively reduce these infections, a multi-sectoral effort is needed. Preventive measures should include good hygienic practices, good animal husbandry practices, heightened provision of educational health programs, health services in all governorates including rural areas. Furthermore, it is also essential to find radical solutions to the recent water crises in Yemen.